Answer:
c=5-ab is the correct one.
Step-by-step explanation:
Answer:
B
Step-by-step explanation:
Use the Heron's formula for the area of the triangle:
where a, b, c are lengths of triangle's sides and
Since then
Hence,
Answer:
Choice b is correct.
Step-by-step explanation:
We have given the sides of triangle.
a = 11.5, b = 13.7 and c = 12.2
We have to find the area of the triangle.
The formula to find the area of the triangle when three sides are given is:
A = √p(p-a)(p-b)(p-c)
where p = (a+b+c) / 2
p = (11.5+13.5+12.2)/2
p = 18.7
A = √18.7(18.7-11.5)(18.7-13,7)(18.5-12.2)
A = 30√4.862 units²
A≈ 66.1 units²
Answer:
Step-by-step explanation:
We have been given an polynomial and we are asked to factor our given polynomial.
We will factor our given polynomial by splitting the middle term in two numbers such that the numbers add up-to -15 and their product will be equal to 36.
We know that -12 and -3 add up-to -15 and their product is 36. So splitting the middle term of our given polynomial we will get,
Therefore, the factored form of our given polynomial is .
The factored form of the polynomial is .
To find the factored form of the polynomial , we can look for two binomials that, when multiplied, give us the original polynomial.
The general form of a quadratic polynomial in factored form is
where and are the roots of the polynomial.
Now, find two numbers whose product is 36 and whose sum is -15.
The numbers that satisfy these conditions are -3 and -12,
since and
Therefore, we can factor the polynomial as:
So, the factored form of the polynomial is .
To learn more on Polynomials click:
#SPJ6
a=b(1/c-1/d)
Answer: c = b/(a + 1).
Step-by-step explanation:
a = b(1/c - 1/d)
Expand RHS by first finding LCM
a = b((d — c)/cd)
a = (bd — bc)/cd
Then cross multiply
acd = bd — cd
Collect the terms having c to the LHS
acd + cd = bd
Factorise cd out of LHS
( a+ 1)dc = bd
c = bd/(a + 1)d
c = b/(a + 1).
–46
B.
46
b. { -2 ≤ x ≤ 2}
c. { -2 ≤ x ≤ 1 }
d. { -1 ≤ x ≤ 1 }
e. { 0 ≤ x ≤ 1 }
Tolong caranya...
The solution to the given inequality, |2x + 1| ≤ 3, is the set { -2 ≤ x ≤ 1 }, which corresponds to answer choice (c). This is achieved by solving two separate inequalities, 2x + 1 ≤ 3 and - (2x + 1) ≤ 3.
The subject of the question is Mathematics, specifically a High School algebra topic on solving absolute inequalities. The student's question is asking us to solve the inequality |2x + 1| ≤ 3. To do this, we need to create and solve two separate inequalities: 2x + 1 ≤ 3 and - (2x + 1) ≤ 3.
Solving 2x + 1 ≤ 3 gives us 2x ≤ 2 and x ≤ 1 . Solving - (2x + 1) ≤ 3 gives us -2x - 1 ≤ 3 , then -2x ≤ 4 , and finally x ≥ -2 . Combining these answers gives us the solution set { -2 ≤ x ≤ 1 }, which corresponds to answer choice (c).
#SPJ3